Solve for m -3(6m-6)=144

Math
-3(6m-6)=144
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3(6m-6)=144 by -3.
-3(6m-6)-3=144-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3(6m-6)-3=144-3
Divide 6m-6 by 1.
6m-6=144-3
6m-6=144-3
Divide 144 by -3.
6m-6=-48
6m-6=-48
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Add 6 to both sides of the equation.
6m=-48+6
Add -48 and 6.
6m=-42
6m=-42
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6m=-42 by 6.
6m6=-426
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6m6=-426
Divide m by 1.
m=-426
m=-426
Divide -42 by 6.
m=-7
m=-7
Solve for m -3(6m-6)=144

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top